Latin American Agricultural Workers' Job Demands and Resources and the Association With Health Behaviors at Work and Overall Health - Schwatka, Natalie V.; Jaramillo, Diana; Dally, Miranda; Krisher, Lyndsay; Dexter, Lynn; Butler-Dawson, Jaime; Clancy, Rebecca; Fisher, Gwenith G.; Newman, Lee S. (Frontiers in Public Health, 2022)
In the present study, we describe the job demands and job resources (JD-R) experienced by agricultural workers in three Latin American countries and their relationship to proactive health behaviors at work and overall health. Following previous research on the JD-R model, we hypothesized that job demands (H1) would be negatively related to agricultural workers’ self-reported overall health. On the other hand, we hypothesized that job resources (H2) would be positively related to agricultural workers’ overall health. Furthermore, we hypothesized (H3) that workers’ engagement in jobsite health promotion practices via their proactive health behaviors at work would partially mediate the relationship between workers’ job resources and job demands and overall health. We also had a research question (R1) about whether there were differences by type of job held. The sample of workers who participated in this study (N = 1861) worked in Mexico, Guatemala, and Nicaragua for one large agribusiness that produces sugar cane. They worked in two distinct areas: company administration and agricultural operations. We administered employee health and safety culture surveys using survey methods tailored to meet the needs of both types of workers. Stratified path analysis models were used to test study hypotheses. In general, we found support for hypotheses 1 and 2. For example, operations workers reported more physically demanding jobs and administrative workers reported more work-related stress. Regardless, the existence of high job demands was associated with poorer overall health amongst both types of workers. We found that workers in more health-supportive work environments perform more proactive health behaviors at work, regardless of their role within the organization. However, hypothesis 3 was not supported as proactive health behaviors at work was not associated with overall health. We discuss future research needs in terms of evaluating these hypotheses amongst workers employed by small- and medium-sized agribusinesses as well as those in the informal economy in Latin America. We also discuss important implications for agribusinesses seeking to develop health promotion programs that meet the needs of all workers.